SURVEILLANCE AND PREVENTION OF RADICALIZATION AMONG RETIRED INDONESIAN MIGRANT WORKERS: A HOLISTIC APPROACH TO NATIONAL SECURITY IN NORTH SULAWESI - Pinta Simamora; Grenaldo Ginting; Pingkan Kaunang; Joni Kutu' Kampilong; Angereine Pinontoan; Hanzel Mamuaya (SOSIOEDUKASI, 2025)
Indonesia's labor migration creates a huge amount of remittances, but the recall (PMI Purna) is vulnerable. In North Sulawesi, repatriated workers are economically marginalized, face psychosocial loads, geopolitical vulnerabilities, and risk becoming radicalized. This study analyzes the influences of vulnerability, institutional lacunae, and policy options on preventative supervision. A mixed method sequenced explanatory study was adopted, combining normative–normative--juridical analysis and fieldwork in Manado, Sangihe, Talaud, and Bitung. Consultations with stakeholders, focus group discussions, 100 interviews with returnees, and observations, were used for data collection. Thematic analysis identified patterns of deprivation, stigma and institutional fragmentation from repetition across the different case studies. Findings show that there is a regulatory micronucleus between Law No. 18/2017 (labor protection) and Law No. 5/2018 (counter-terrorism), placing ordinary returnees in a "grey zone." The region is succumbing to economic failure, as seen in the 68% unemployment rate and failure of many businesses, psychosocial distress, with 45% depression and anxiety, stigma in 32% exclusion, porous borders, and kinship ties with Mindanao. Reintegration programs focus on entrepreneurship but do little on psychological resilience, and agencies work in silos where there is very little data sharing. This study adds a new proposition to the literature by providing a hybrid model that incorporates economic, psychological, and geopolitical dimensions. Practically, it is necessary to identify psychosocial debriefing, community-based detection, and digital literacy. The policy recommendations include policy coverage, institutional integration, the creation of border economic zones, and the implementation of digital immunization strategies. Hence, effective reintegration is Indonesia’s wall against radicalization.